Wisteria floribunda agglutinin‐positive Mac‐2 binding protein predicts early occurrence of hepatocellular carcinoma after sustained virologic response by direct‐acting antivirals for hepatitis C virus. Issue 13 (23rd August 2018) - Yasui, Yutaka; Kurosaki, Masayuki; Komiyama, Yasuyuki; Takada, Hitomi; Tamaki, Nobuharu; Watakabe, Keiya; Okada, Mao; Wang, Wan; Shimizu, Takao; Kubota, Yohei; Higuchi, Mayu; Takaura, Kenta; et al.
Abstract : Aim: The aim of this study is to clarify the value of serum Wisteria floribunda agglutinin‐positive Mac‐2 binding protein (WFA + ‐M2BP) for predicting hepatocellular carcinoma (HCC) in chronic hepatitis C patients who achieved sustained virologic response (SVR) by therapy with interferon‐free, direct‐acting antivirals (DAAs). Methods: This is a retrospective cohort study that included 567 patients who underwent antiviral therapy with an interferon‐free DAA regimen and achieved SVR. Serum WFA + ‐M2BP was measured after SVR. Factors predictive of HCC occurrence and recurrence were analyzed in the patients after stratification by previous treatment history of HCC. Results: Among 518 patients who had no history of HCC, 13 developed HCC. Post‐SVR WFA + ‐M2BP ≥1.75 cut‐off index (C.O.I., P < 0.001) and α‐fetoprotein (AFP) level ≥6 ng/mL ( P = 0.01) were significant predictors of HCC development. Multivariate analysis showed that post‐SVR WFA + ‐M2BP ≥1.75 C.O.I. was an independent factor significantly associated with the development of HCC (hazard ratio [HR] 6.0; 95% confidence interval (CI), 1.8–19.4; P = 0.003). Among 49 patients who had a previous history of HCC, 22 had recurrence after SVR. Post‐SVR AFP ≥6 ng/mL was the only factor associated with recurrence‐free survival (HR 3.1; 95% CI, 1.3–7.5; P = 0.01). Conclusions: Post‐SVR WFA + ‐M2BP is a predictive factor for the development of HCC in patients with no previous HCC history and treated with DAAs. Post‐SVR AFP was predictive for HCC recurrence after DAA therapy.